Inhibiting and Driving Factors of Bureaucratic Reform in Regional Government in Indonesia: A Literature Review - Nikki Mulya; Roy Valiant Salomo (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2026)
The Bureaucratic Reform (RB) program in Indonesia has been running for more than 15 years. Since its inception through Presidential Regulation (Perpres) Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010-2025, RB has gone through three roadmap stages, which represent five-year targets. The average RB index value indicates a gap in achievement between Ministries/Agencies, Provinces, and Regencies/Cities. A visible trend is that the further the level of government is from the central government, the lower the average RB index value. To achieve good governance, a change strategy is necessary. This change strategy is also known as administrative reform, or in Indonesia better known as bureaucratic reform. The purpose of this study is to identify central issues related to inhibiting and driving factors for bureaucratic reform in local governments in Indonesia. The research method used is a literature review of 15 articles obtained and selected from Scopus and Garuda. The literature analysis concluded that the main factors inhibiting RB in local governments are suboptimal civil servant (ASN) management, a patrimonial culture, and weak organizational adaptability. The main driving factors are highly committed leadership and the readiness of civil servants to change in the digital era based on information technology.